2017
DOI: 10.3847/1538-4357/aa71b8
|View full text |Cite
|
Sign up to set email alerts
|

Hints for Small Disks around Very Low Mass Stars and Brown Dwarfs

Abstract: The properties of disks around brown dwarfs and very low mass stars (hereafter VLMOs) provide important boundary conditions on the process of planet formation and inform us about the numbers and masses of planets than can form in this regime. We use the Herschel Space Observatory PACS spectrometer to measure the continuum and [O I] 63 μm line emission toward 11 VLMOs with known disks in the Taurus and ChamaeleonI star-forming regions. We fit radiative transfer models to the spectral energy distributions of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 71 publications
7
48
1
1
Order By: Relevance
“…Disk Size.The characteristic temperature at which the disk emits depends on the spatial distribution of dust, in particular disk size (e.g., Hendler et al 2017). Spatially resolved millimeter observations show that protoplanetary disks vary in size by an order of magnitude (e.g., Andrews et al 2010, s » 0.4 dex).…”
Section: Mass Accretion Rates and Disk Masses: Current Status And Posmentioning
confidence: 99%
“…Disk Size.The characteristic temperature at which the disk emits depends on the spatial distribution of dust, in particular disk size (e.g., Hendler et al 2017). Spatially resolved millimeter observations show that protoplanetary disks vary in size by an order of magnitude (e.g., Andrews et al 2010, s » 0.4 dex).…”
Section: Mass Accretion Rates and Disk Masses: Current Status And Posmentioning
confidence: 99%
“…Testi et al (2016) found evidence that two discs of VLM objects in Ophiuchus may have sharp outer disc radii of ≈ 25 au, with three other discs having radii between 50 and 150 au, depending on model parameters. From modelling spectral energy distributions, Hendler et al (2017) find that out of 11 young stars with masses M * ∼ < 0.2 M , 7 likely have disc radii smaller than 10 au, with the remaining four objects having radii from 10-80 au.…”
Section: Disc Properties Versus Stellar Massmentioning
confidence: 99%
“…The exact dependence, however, is model dependent, for example, whether or not disc temperature is scaled with stellar luminosity, and the assumptions made about the disc size; see, for example, Pascucci et al (2016);Hendler et al (2017). Andrews et al (2013) found that the millimetre flux scales as Fmm ∝ M 1.5−2.0 * for Class II discs in the Taurus region and they argue that, accounting for dust temperature scaling, this supports a roughly linear scaling of disc mass with stellar mass (i.e.…”
Section: Disc Properties Versus Stellar Massmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopted the opacity law from Beckwith et al (1990) and the dust temperature using the prescription from Andrews et al (2013), which calculates a characteristic dust temperature in the outer regions of a disk surrounding a star of a given luminosity. This approach gives the most conservative upper limit for the dust mass (a higher T dust , as might be expected for a disk smaller than the 200 au assumed in Andrews et al, would result in a lower dust mass upper limit, see Hendler et al 2017). We do not attempt a more precise calculation of the dust temperature for each disk, e.g., via radiative transfer calculations, because the uncertainty on the dust mass estimate is dominated by the uncertainty on the dust opacity coefficient κ ν .…”
Section: Upper Limits On the Mass Of Dust Orbiting Youngmentioning
confidence: 99%